Intrinsic Motivation and Incentives - Prendergast, Canice (American Economic Review, 2008)
Workers act in the interests of their employ? ers for a host of reasons. Sometimes money is the motivation, but often it is because they care about what they do. Despite the importance of such intrinsic motivation, the economic litera? ture has offered little in terms of understanding relevant trade-offs when alignment of inherent preferences (rather than monetary interests) is what motivates people.1 Instead, the literature has focused largely on the efficiency gains that arise from agents sharing the preferences of their employers.2 This paper offers such a theory of intrinsic motivation, where firms partially solve agency problems by hiring agents with particu? lar preferences. Unlike the previous literature, I show that firms, in general, hire agents who do not share their interests?instead, agents are disproportionately motivated to carry out a sub? set of what the firm cares about. Specifically, I show that the institution hires the agent with similar preferences to himself only in the limit? ing case where the agent's preferences are irrel? evant?namely, when output can be perfectly contracted on. Instead, the optimal response of the institution is to hire biased agents, with the degree of bias increasing as mea? sures get worse. The reason for this is rather simple?that jobs within firms are specialized. So, for example, some people make things, others design them, yet other sell them, and so on. Similarly, aca? demics do research, deans raise money, admin? istrators do the books, social workers provide services to clients while their superiors are charged with cost control, etc. The principal novelty of this paper is to show how hiring practices?and specifically the intrinsic moti? vation of those hired?changes as the ability to contract worsens in a world where tasks are specialized. In doing so, it paints a picture of firms responding to noncontractibility by hiring agents with very extreme interests, at the cost of their ignoring other aspects of their jobs. So, for example, if the output of a social worker cannot be measured, a natural response will be to hire agents who are highly motivated to get benefits to clients, at the cost of their ignoring things like cost control. Simple though this observation is, it illustrates a cost to using intrinsic motiva? tion?namely, the endogenous hiring of those who increasingly care only about one aspect of their job. In this way, the simple model outlined here lays the foundation for a view of poor contracting firms as fiefdoms, where those with extreme competing interests reside, a point I elaborate on elsewhere (Prendergast 2008). For a theory of intrinsic motivation to be use? ful, firms must have some control over it. The central assumption here is that firms have some ability to hire employees based on these intrin? sic preferences. I build a model of an institution that carries out two activities?say, service pro? vision and cost control. It employs two agents to do so. The tasks are somewhat specialized, in that one agent primarily (but not exclusively) does service provision and the other primarily does cost control. The institution has an objec? tive that trades off these two components and has a performance measure that can reward agents. The firm also chooses whom to hire. Potential * Discussant: Robert Gibbons, Massachusetts Institute of Technology.